Awake Surgical Mitral Valve Repair after Transcatheter Aortic Valve Replacement - Hirofuji, Aina; Kanda, Hirotsugu; Kitani, Yuya; Kamiya, Hiroyuki (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Transcatheter aortic valve replacement has become a popular choice for cases with severe aortic stenosis. However, when severe mitral regurgitation is comorbid in high-risk patients with severe aortic stenosis, therapeutic options must be weighed for each case. Here we present a very frail 88-year-old patient with severe aortic stenosis and severe mitral valve regurgitation who underwent a successful awake minimally invasive mitral valve repair after transcatheter aortic valve replacement.
Keywords: aortic stenosis; mitral regurgitation; transcatheter aortic valve replacement; minimally invasive cardiac surgery